Intensive care nurses’ knowledge and practice of evidence-based recommendations for endotracheal suctioning: a multisite cross-sectional study in Changsha, China - Chen, Wenjun; Hu, Shuang; Liu, Xiaoli; Wang, Nina; Zhao, Junqiang; Liu, Peng; Chen, Kaixia; Hu, Jiale (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Endotracheal suctioning is one of the most frequently performed invasive procedures by intensive care nurses. Nurses should have adequate knowledge and skills to perform endotracheal suctioning based on the best evidence. Little is known about intensive care nurses’ knowledge and practice of evidence-based endotracheal suctioning in Chinese hospitals. The purpose of this study was to investigate intensive care nurses’ knowledge and practice of evidence-based recommendations regarding endotracheal suctioning. Specifically, the study aimed to examine (1) intensive care nurses’ awareness of and adherence to endotracheal suctioning guidelines and (2) factors influencing their level of awareness and adherence. Methods A cross-sectional survey of 310 staff nurses working in intensive care units was carried out at Changsha, China. Data on participants’ characteristics, awareness of, and adherence to the endotracheal suctioning guidelines were collected through online questionnaires. Following univariate descriptive statistics, the Mann–Whitney U test and Kruskal–Wallis H test were performed using Software Package Statistical Analysis Version 23.0. Results A total of 281 nurses completed and returned the survey (response rate = 90.6 %). One-half to three-quarters of the nurses knew 21 of the 26 evidence-based practices and believed their practices followed the guidelines. Over half of them were unaware of the difference between open and close suctions and the pros and cons of using hyperinflation. Almost 50 % of nurses believed some of their clinical practices did not follow the evidence-based recommendations, such as not routinely using normal saline and using 80–120 mmHg suction pressure during endotracheal suctioning. Nurses with endotracheal suctioning training demonstrated significantly higher awareness of endotracheal suctioning recommendations and higher adherence levels than untrained nurses. Conclusions The study findings revealed that Chinese intensive care nurses lacked awareness of several essential evidence-based endotracheal suctioning practices, and there were gaps between their current practice and the guideline recommendations. Further research should emphasize revealing barriers and facilitators of implementing evidence-based endotracheal suctioning practices as well as developing context-suitable interventions for guideline implementation.